Identification module (matlab simulink) - 383169 Vijendran Paripanapan (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Mechatronics)) - Universiti Teknologi Malaysia, 2003